2015
DOI: 10.1182/blood.v126.23.1534.1534
|View full text |Cite
|
Sign up to set email alerts
|

Third Generation CD19-CAR T Cells for Relapsed and Refractory Lymphoma and Leukemia Report from the Swedish Phase I/IIa Trial

Abstract: Chimeric antigen receptor (CAR) T cells have shown promising results in patients with B cell malignancy. In preclinical studies we showed that CD19-targeting third generation (3G) CAR T cells containing signaling domains from both CD28 and 4-1BB as co-stimulatory molecules have greater activation and proliferation in response to antigens than 2G CARs containing CD28 only. Herein we report results from a phase I/IIa study (NCT:02132624) using these 3G CAR T cells. Patients with relapsed or refractory CD19+ B-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Elevated bAR signaling was associated with reduced IFNg production and cytolytic killing by CD8 þ T cells in response to anti-4-1BB and anti-PD-1 antibody treatments, demonstrating possible mechanisms for reduced therapeutic efficacy. Anti-PD-1 antibodies are approved for use in a number of cancer settings and 4-1BB targeting is currently being tested in clinical trials on several cancer types, including melanoma, non-small cell lung cancer, leukemia, and lymphoma (38)(39)(40)(41). This raises the possibility that neural signaling might affect treatment response in diverse patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated bAR signaling was associated with reduced IFNg production and cytolytic killing by CD8 þ T cells in response to anti-4-1BB and anti-PD-1 antibody treatments, demonstrating possible mechanisms for reduced therapeutic efficacy. Anti-PD-1 antibodies are approved for use in a number of cancer settings and 4-1BB targeting is currently being tested in clinical trials on several cancer types, including melanoma, non-small cell lung cancer, leukemia, and lymphoma (38)(39)(40)(41). This raises the possibility that neural signaling might affect treatment response in diverse patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…To further amplify the activation signal, efforts to combine 2 costimulatory domains into 1 CAR molecule, which denotes the 3rd-generation CAR T cells (Fig. 3C), has been reported; however, a pilot clinical trial that assessed CD28-4-1BB double costimulatory domain CAR T cells (ClinicalTrials.gov: NCT02132624) achieved only a 54.5% CR rate in 11 patients with B cell malignancy, as reported in the 2015 American Society of Hematology meeting [71]. As excessive signaling can lead to CAR T cell exhaustion, it is still unclear whether the boosted signaling with 2 costimulatory domains would generate more favorable results.…”
Section: Promote Cart19 Expansion and Persistencementioning
confidence: 97%
“…Here, we engineered NK-92 cells to express a third generation CD4-specific CAR (CD4CAR) containing CD28, 4-1BB and CD3ζ signaling domains, because third-generation CAR constructs have been associated with enhanced antitumor activity [ 40 , 41 ]. We found that CD4CAR NK-92 cells exhibit robust anti-tumor cytotoxicity ex vivo against both adult and pediatric CD4 + lymphoma/leukemia cell lines, CD4 + T-cells isolated from umbilical cord blood, as well as against untreatable primary CD4 + T-cell malignancies from adult and pediatric patients.…”
Section: Introductionmentioning
confidence: 99%